When agency "fits" regardless of gender: Perceptions of applicant fit when job and organization signal male stereotypes - Regina Dutz; Sylvia Hubner; Claudia Peus (Personnel Psychology, 2021)
Evaluators' fit assessments are not only influenced by applicants' qualities, but also by stereotypes, especially in recruitment for high-status jobs in male-dominated fields. The unidimensional agentic stereotype of these work contexts signals agentic job and organizational requirements (stereotypically male qualities such as achievement orientation), although the actual requirements usually also include communality (stereotypically female qualities such as interpersonal skills). In five experiments, we investigate the relevance of perceived applicant agency for perceived applicant fit, the influence of recruitment material, contextual differences, and the role of applicant gender. Our findings indicate that perceived applicant agency drives perceived person-job and person-organization fit in strictly male stereotyped work contexts, regardless of gender, and agentic recruitment material enhances this effect. Contrasting different contexts (high- with low-status jobs and a male-dominated with a gender-balanced and female-dominated field) revealed that the relevance of perceived agency increases with perceived job status, and the relevance of perceived communality decreases with the expected share of men. Although women were perceived as highly agentic in strictly male stereotyped work contexts, their need to be perceived as agentic also was higher than for men, due to the perceived lack of fit between women and high-status jobs.
Keywords: 650; gender/sexual orientation; person-environment fit; recruitment; stereotypes